Learning management systems for higher education: a brief comparison - Lisseth Sanchez; Jefferson Penarreta; Xavier Soria Poma (Springer, 2024)
Abstract The learning management system (LMS) is a software based on SAAS, internet navigator, or user application, which manage the teaching and learning of an academic or non-academic program. This work presents a comparison of 45 LMSs. The objective of this research is to report a study of the LMS developed for higher education. This objective is addressed by considering all LMSs with online access to information. For the comparison study, an evaluation criteria has been developed based on the literature review from the past 20 years. This evaluation methodology is based on Software Quality and Teaching-Learning tools for online educational platforms (SQTL), it is composed by six criteria: interoperability, accessibility, productivity tools, communication tools, learning tools, finally with the security standards and certifications. The maximum sum of SQTL score is 10 points and the minimum 0. The best LMS according to the comparison are Paradiso and Moodle with 9.50 and 9.25 points, respectively. Paradiso has around 1 million users and Moodle over 250 millions. The Google Sheets with the collected raw data and SQTL scores are available in  https://shorturl.at/wqDWk .